Early language intervention improves behavioral adjustment in school: evidence from a cluster randomized trial - West, G; Lervåg, A; Snowling, MJ; Buchanan-Worster, E; Duta, M; Hulme, C (Elsevier, 2022)
Oral language skills are critical for psychosocial development and children with language difficulties are more likely than peers to experience behavioral problems. This study investigated the effects of an oral language intervention on behavioral adjustment. We collected teacher ratings of behavioral adjustment for 1173 children taking part in a cluster randomized trial of the Nuffield Early Language Intervention (NELI) program in 193 primary schools. Ratings were collected before and immediately after the 20-week intervention. Children receiving the language program showed significantly greater improvements than the untreated control group on a latent variable reflecting behavioral adjustment (d = 0.23). However, the improvements in behavioral adjustment for children receiving language intervention were not mediated by improvements in language. We suggest that the improvements in behavioral adjustment are a consequence of the small group and individual teaching sessions in the language intervention program, which emphasizes the need to pay attention and regulate behavior. This emphasis appears to produce generalized improvements in children's behavior regulation outside of the targeted language teaching sessions.